2021
DOI: 10.1111/1365-2656.13412
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social structure and management on risk of disease establishment in wild pigs

Abstract: Contact heterogeneity among hosts determines invasion and spreading dynamics of infectious disease, thus its characterization is essential for identifying effective disease control strategies. Yet, little is known about the factors shaping contact networks in many wildlife species and how wildlife management actions might affect contact networks. Wild pigs in North America are an invasive, socially structured species that pose a health concern for domestic swine given their ability to transmit numerous devasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…The estimated R 0 ranged from 1.11 to 2.37 with a mean of 1.54, which was similar to the estimates from previous studies [ 11 29 30 31 ]. However, the current study revealed spatiotemporal variations in the values.…”
Section: Discussionsupporting
confidence: 87%
“…The estimated R 0 ranged from 1.11 to 2.37 with a mean of 1.54, which was similar to the estimates from previous studies [ 11 29 30 31 ]. However, the current study revealed spatiotemporal variations in the values.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, kinship was shown to drive bovine tuberculosis infections in badger cubs exposed to infectious females in a natal sett (Benton et al, 2016). Inter-group contacts in wild boar occur most frequently at a spatial scale similar to interactions within groups Yang et al, 2020). This spatial overlap in social connectivity may confound the effects of inter-vs. intra-group transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Wild boar social structure is based on cohesive, matrilineal social units (Gabor et al, 1999;Kaminski et al, 2005;Podgórski et al, 2014b). Contact rates are strongly structured socially and spatially Yang et al, 2020). The rate of inter-group interactions is relatively low and declines sharply with distance between the groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If instruments are not deployed in proportion to local host densities, then areas with a higher ratio of collars to animals may be flagged as potential transmission hubs due to sampling alone. There are statistical methods for drawing inference from partially-observed contact data (e.g., Cross et al 2013;Yang et al 2021), but higher collar densities may also be necessary in some settings (Gilbertson, White, & Craft 2021). Scaling up from individuals to populations often requires information about inter-individual attraction, along with auxiliary data on population densities or group sizes.…”
Section: Next Stepsmentioning
confidence: 99%